Rancang Bangun Alat Meteran Air berbasis Internet of Things (IoT) pada Rumah Tangga - Jefri, Jefri; Huda, Yasdinul (TSAQOFAH, 2025)
Issues in conventional water metering systems, such as delayed recording and data inaccuracy, highlight the need for technological innovation in managing household water consumption. This study aims to design and implement an Internet of Things (IoT)-based water meter device that enables real-time and remote monitoring of water usage. The method used is prototyping, involving the development of a system composed of hardware components such as the NodeMCU ESP8266, water flow sensor, and solenoid valve, alongside software tools including Arduino IDE and the Blynk application. The prototype was tested through ten water flow measurements and compared against readings from a conventional meter. The results show an average error rate of 1.27% and a Pearson correlation coefficient of 0.9989, indicating a very high level of empirical validity. The study concludes that the device effectively provides accurate and automated water consumption monitoring via a mobile application and is suitable as an efficient and adaptive alternative to conventional water meters, aligning with the demands of the Fourth Industrial Revolution.